2022
DOI: 10.1177/09544119221075140
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization of functionally graded lattice infill total hip arthroplasty stem for stress shielding reduction

Abstract: Reducing stress shielding of stem-inserted femurs in total hip arthroplasty caused by the high stiffness of the stem is an emerging medical engineering issue. In this study, a numerical design optimization methodology lattice infill stem was developed to realize a stem, balancing the low stiffness and strength requirements. Two pairs of models and loading conditions were introduced for the stress shielding and strength criteria. The objective function was set as the weighted sum of the criteria. Its effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Saravana et al (2017) used the comparison of stress present in the femur before and after implantation, namely SSI, as their objective function taking yield and stress, and elastic modulus into consideration for the optimization [ 64 ]. A similar approach was applied in a study presenting a hip stem design based on optimized stress shielding and compliance [ 65 ]. Gao et al (2022) designed a femoral stem consisting of eight porous segments maximizing the stress transferred to the surrounding bone [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Saravana et al (2017) used the comparison of stress present in the femur before and after implantation, namely SSI, as their objective function taking yield and stress, and elastic modulus into consideration for the optimization [ 64 ]. A similar approach was applied in a study presenting a hip stem design based on optimized stress shielding and compliance [ 65 ]. Gao et al (2022) designed a femoral stem consisting of eight porous segments maximizing the stress transferred to the surrounding bone [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fatigue performance, which influences implant longevity, was factored into topology optimization schemes in several studies. This included a fatigue safety factor as a boundary condition [ 57 , 58 , 60 , 61 ], optimizing the design until a suitable factor of safety was achieved [ 67 ], or by comparing the occurring stress in the porous design to the respective fatigue strength of the selected material [ 62 , 65 ]. Considering fatigue strength in the optimization as a boundary condition enables the design of a graded porous design with reduced stiffness and sufficient mechanical strength.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recent developments in additive manufacturing (AM) and selective laser melting (SLM) using biocompatible Ti-6Al-4V (Ti64) powder have expanded the applications of metal AM to medical implants. This advancement is primarily attributed to AM's capability to produce complex geometries that were not possible using conventional subtractive manufacturing [1][2][3][4]. Additively manufactured patient-specific medical devices have the benefit of matching individual patient's bone anatomy due to the high customizability of AM process [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Therefore, stainless steel and titanium alloys are still most widely used biomaterials for bone plate, although they often led to the stress shielding effect because of their large elastic modulus. [13][14][15] The existing studies shown that the stress shielding effect can be reduced by the optimal design of implant, [16][17][18][19] some researchers tried to overcome the constraints of materials by improving the structure of bone plates. Bottlang et al 20 designed an active plate, which can achieve dynamic stabilization after bone apposition with six elastically suspended locking screws.…”
Section: Introductionmentioning
confidence: 99%